IL-33 in Rheumatic Diseases - Dong, Yuanji; Zhong, Jixin; Dong, Lingli (Frontiers in Medicine, 2021)
Interleukin-33 (IL-33) is a nuclear factor mainly expressed in barrier epithelium, endothelial cells, and fibroblast reticular cells. Some inflammatory cells also express IL-33 under certain conditions. The important role of IL-33 in allergic reactions, helminth infection, cancer, tissue fibrosis, chronic inflammation, organ transplantation, and rheumatic immune diseases has been extensively studied in recent years. IL-33 primarily activates various circulating and tissue-resident immune cells, including mast cell, group 2 innate lymphoid cell (ILC2), regulatory T cell (Treg), T helper 2 cell (Th2), natural killer cell (NK cell), and macrophage. Therefore, IL-33 plays an immunomodulatory role and shows pleiotropic activity in different immune microenvironments. The IL-33/serum stimulation-2 (ST2) axis has been shown to have a detrimental effect on rheumatoid arthritis, systemic lupus erythematosus, and other rheumatic diseases. Interestingly, IL-33 also plays a protective role in the repair of barrier epithelium and the activation of Tregs. Therefore, the role of IL-33/ST2 depends on the underlying pathological conditions in rheumatic diseases. This review focuses on the dual role of the IL-33/ST2 axis in rheumatic diseases.